Sweetpotato production practices, constraints, and variety evaluation under different storage types. (18th November 2020) - Abrham, Tinsae; Beshir, Hussien Mohammed; Haile, Ashenafi
Abstract: Sweetpotato plays an important role in ensuring food security and household income sources for local communities in Ethiopia. It is dominantly grown in southern parts of Ethiopia. However, its production and productivity over the last few years has declined due to the limited access of quality planting materials at the onset of the rainy season, disease, and severe pest infestation. Therefore, it was imperative to carry out this study to identify the main constraints related to the recent decline of the crop in Misrak Badawacho District. The survey result revealed that many varieties of sweetpotato were grown in the district; mainly, Awassa‐83, Ogan‐Sagan, and Wolaita‐local were the most preferred variety by producers. The main sweetpotato production and storage constraints in the study district are as follows: rodents, disease and insect pests, heat and drought, shortage of quality planting materials, and absence of best methods for long‐term storage. Awassa‐83, Ogan‐Sagan and Wolaita‐local were evaluated under different storage types (straw, soil, ash, sawdust, and sand storage). The combination of Awassa‐83 variety and sand storage was performed better in percentage of decay, weight loss, and weevil damage, whereas length and number of vine per storage roots were performed better in the separate treatment. Thus, Awassa‐83 variety and sand storage can be recommended for maintaining the storage roots during dry periods and access of quality vines at the onset of the rainy season. More importantly, sand storage provides an opportunity to maintain the quality of sweetpotato storage roots for a long period of time and producers can easily and timely access quality vines at the onset of rainy season. Abstract : Although sweetpotato is one of the major food security crops in Ethiopia, its production and productivity is constrained by the limited access of quality planting material at the onset of the rainy season.